THE RELATIONSHIP BETWEEN PEAK EXPIRATORY FLOW RATE BEFORE BRONCHOSCOPY AND ARTERIAL OXYGEN DESATURATION DURING BRONCHOSCOPY - D. Attaran; M. Towhidi; M. Amini M. Toosi (Acta Medica Iranica, 2008)
A significant reduction in arterial blood oxygen saturation during fiberoptic bronchoscopy has been proved but it is not yet known whether all patients need supplemental oxygen during this procedure. The aim of study is to examine the relationship between peak expiratory flow rate (PEFR) before bronchoscopy and oxygen desaturation during bronchoscopy. Measurement of PEFR (% predicted) performed before bronchoscopy and arterial O2 desaturation was assessed with a pulse oximeter during bronchoscopy. Study performed in 66 patients with a median age 53 years, who had been referred to our bronchoscopy unit. None of the patients received supplemental oxygen before the procedure. Thirty nine cases (59%) had an episode of O2 desaturation during bronchoscopy. Of them 25 cases (38%) had sustained O2 desaturation, requiring oxygen therapy while 14 cases (21%) had momentary desaturation (< 20s) not requiring O2 therapy. Oxygen therapy was administered in 58% of cases with PEFR % < 60 and in 83% of cases with PEFR % less than 45 (P, 0.008 and 0.001, respectively). We also observed a significant fall in mean O2 saturation during bronchoscopy (88 ± 4 %) compared to prebronchoscopy levels (95 ± 2 %) (P < 0.0001). It is concluded that PEFR < 60% and especially < 45% is a reliable predictor of hypoxemia and the need to O2 therapy during bronchoscopy.